What Level of Fixed Costs Can Reconcile Consumption and Stock Returns? - Luttmer, Erzo G. J. (Journal of Political Economy, 1999)
This paper proposes a lower bound on the level of fixed transaction costs that is required for observations on consumption choices to be consistent with data on asset returns and a given set of preferences. The bound is derived from necessary conditions for the optimality of consumption choices in the presence of fixed transaction costs. These conditions reduce to standard Euler equations when transaction costs are zero. Conservative point estimates suggest that a consumer with log utility who consumes U. S. per capita consumption and who can trade in U. S. Treasury bills and an index of New York Stock Exchange stocks must face a fixed transaction cost of at least 3 percent of monthly per capita consumption. This lower bound declines rapidly with increases in risk aversion or when certain restrictions on short selling are included.